2020
DOI: 10.1007/s00345-020-03133-y
|View full text |Cite
|
Sign up to set email alerts
|

Early recovery after surgery for radical cystectomy: comprehensive assessment and meta-analysis of existing protocols

Abstract: Purpose Different enhanced recovery after surgery (ERAS) protocols (EP) for radical cystectomy (RC) have been published. Protocols highly differ in number of included items and specific measures. Materials and methods A systematic review and meta-analysis on EPs in RC were performed using the databases MedLine, Cochrane Library, Web of science, and Google Scholar. The specific ERAS measures of the protocols were extracted, analyzed, and compared. Pooling of available outcome data was performed for length of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 48 publications
3
24
0
1
Order By: Relevance
“…Multivariate analysis results identified time to mobilization, time to fluid intake, and low G‐8 score as independent risk factors of POI after ICUD. Consistent with these results, most modern ERAS protocols reportedly enhance early mobilization and early oral feeding, which have shown a substantial reduction of GI complications 16,17 …”
Section: Discussionsupporting
confidence: 58%
“…Multivariate analysis results identified time to mobilization, time to fluid intake, and low G‐8 score as independent risk factors of POI after ICUD. Consistent with these results, most modern ERAS protocols reportedly enhance early mobilization and early oral feeding, which have shown a substantial reduction of GI complications 16,17 …”
Section: Discussionsupporting
confidence: 58%
“…In our cohort, median LOS was 7 d, with a decrease from 9 to 5 d observed over the study period. It has consistently been shown that enhanced recovery after surgery (ERAS) protocols reduce LOS, and gradual implementation of ERAS principles in our perioperative care over the study period is the likely explanation for this decrease [15] , [16] . Median DAOH increased by 4 d over the study period, reflecting that ERAS protocols reduce the duration of the index hospitalisation, but have limited effects on the postoperative course over the first 3 mo.…”
Section: Discussionmentioning
confidence: 99%
“…surgery, 4 urology, 5 and thoracic surgery. 6 Their implementation within spine surgery is newer, with increasing publications in recent years.…”
mentioning
confidence: 99%